Development of Geography Learning Media in the Form of Digital Magazines with Hydrosphere Dynamics Material - Ferawati Po'u; Fitryane Lihawa; Daud Yusuf (International Journal of Innovation and Education Research, 2023)
This research is learning media development research. The purpose of this research is to produce digital magazine-based learning media on hydrosphere dynamics material. This research uses the development method with the ADDIE model as an approach to developing learning media. In this research there are 5 (five) stages, namely the analysis stage, design stage, development stage, implementation stage, and evaluation stage. The assessment given to each statement, from the media expert validation, stated that it was valid with a rating of 78.18%, the material / content expert stated that it was very valid with a rating of 90%, and the learning expert stated that it was very valid with a rating of 86%. The limited scale trial research conducted by researchers at SMA Negeri 1 Bukal received a good response to the learning media with a result of 79.77%. The results of the general scale trial research conducted at SMA Negeri 1 Momunu received a very good response, student responses from the results of the general scale trial in class X IPS¹ received a score of 82.33% in the valid category, and class X IPS² with an average score of 94.02% in the very valid category. The conclusion of this study is that the digital magazine-based learning media developed by researchers is declared feasible to use in the learning process.